Analisis kinerja sistem produksi pada industri produsen tahu bandung dengan pendekatan simulasi event diskrit: Studi kasus pada Tahu Bandung ALN - Okatria, Luqy Afifah; Kusumastuti, Ratih Dyah (Jurnal Inovasi Pangan dan Gizi, 2024)
Background: This study aims to analyze the performance of the production system currently implemented by Tahu Bandung ALN and propose alternative improvements that can make the performance of the production system more efficient. Methods: This study uses a discrete-event simulation approach, and the parameters of performance used are total production time and total production costs. Finding: The results of the base case scenario simulation found that there are several production processes that have waiting times which indicate the bottlenecks. Therefore, two alternative of improvements are proposed, namely the first scenario (adding more resources in the production processes that have waiting times) and the second scenario (combination of adding more resources in the production processes that have waiting times and implementing the inventory policy of certain raw material). Conclusion: The first alternative scenario is the better one as it can provide an improved performance, in which the total production time is reduced by 22,40% and the total production cost is reduced by 40,57%.